Effect of oligohydramnios on the accuracy of sonographic foetal weight estimation in at term pregnancies - Przemysław Janas; Małgorzata Radoń-Pokracka; Magdalena Nowak; Agata Staroń; Gabriela Wilczyńska; Mirella Brzozowska; Hubert Huras (Elsevier, 2019)
Objective: Ultrasound estimation of foetal weight is a very important aspect of antenatal care. The role of amniotic fluid volume as a potential factor which may impede the relevance of ultrasonographic foetal weight estimation is still questionable. The aim of our study was to evaluate the impact of isolated oligohydramnios on the accuracy of ultrasound foetal weight estimation in at term pregnancies when examination was performed within 48 h before delivery. Materials and methods: The retrospective cohort study included 1831 women with low-risk, singleton, at term pregnancy. Estimated foetal weight (EFW) was calculated using Hadlock-4 formula. Exclusion criteria consisted of multiple pregnancies, active phase of labour, preeclampsia, foetal growth restriction, foetal anomalies, gestational diabetes mellitus and the evidence of intrauterine infection. Isolated oligohydramnios was defined as Amniotic Fluid Index (AFI) ≤50 mm without any other foetal anomalies. EFW and actual birth weight (ABW) were compared by calculation of: absolute error (AE), absolute percentage error (APE) and substantial error (SE) = APE >10%. Results: Participants were divided into 2 groups: Group 1: patients with normal AFI (50 ≤ AFI ≤250 mm; n = 1602) and Group 2: (isolated oligohydramnios, n = 229). There were not observed statistically significant differences between mean ABW and mean EFW in both groups (Group 1: p = 0.525; Group 2: p = 0.317). Mean AE in Group 1 was 221.8 g and 223.1 g in Group 2 (p = 0.919). Mean APE was 6.54% and 6.64% in Group 1 and 2 respectively (p = 0.816). SE ratio was 21.9% in Group 1 and 19.2% in Group 2. Underestimation to overestimation ratio in Group 1 was 1.01 and 0.84 in Group 2. Conclusions: Amniotic fluid volume has limited impact on ultrasound foetal weight estimation. In oligohydramnios group there might be a tendency of overestimation of neonatal ABW. Keywords: Estimated foetal weight, Amniotic fluid index, Ultrasound examination, AFI, EFW